Health Communication and Islam: A critique of Saudi Arabia's efforts to prevent substance abuse - Aljaid, Bandar (2015)
Health communication has gained worldwide recognition as one of the most effective methods for tackling global health challenges; a conclusion that is supported by a range of studies showing generally positive results. Literature in the field has tended to focus on one of two perspectives: either individual behaviour change or a cultural/critical approach. This dissertation, which falls into the latter category, extends previous work on health communication and culture into a new context, namely Saudi Arabia. The thesis is motivated by two main research questions. First, how has culture influenced health communication in Saudi Arabia specifically in initiatives against illicit drug use and alcohol abuse? Second, how has this communication developed? At the heart of this study is the role of Saudi culture in health communication in an increasingly interdependent and connected world. The dissertation makes use of mixed qualitative data collection methods. Principally, it utilised semi-structured interviews with key officials and focus groups with young Saudis and health promoters in Saudi Arabia as well as attendance at and observation of health-communication events and permanent exhibitions as a subordinate method. The study reveals promising findings supporting the growing scholarly interest in the cultural dimension of health communication. It concludes that the key influence of the Saudi culture on health communication against substance abuse is Islamic beliefs about health, in particular those about substance abuse. These beliefs created a rejection of illicit drug abuse in Saudi society, thereby shaping a supportive environment for promotion activities against risky health behaviour. In addition, Islamic influence inspired the related regulations and laws in the kingdom. Islamic and local influences exert a powerful influence on the practical side of health communication in Saudi Arabia, including the content of messages, the appeal used to attract the specific audience, and the communication channels used to promote the campaigns. The study engages with four concepts constituting the Islamic model of health and illicit drug abuse: prohibition (haram), promotion (Da’wah), repentance and inclusiveness (Tawbah), and treatment and rehabilitation (Elaj). The study also examines controversial issues about health communication in the country, such as the predominance of top-down communication, the absence of participatory communication and cultural diversity. In short, a lack of innovation and creativity in delivering health communication messages. The study illustrates the major role the Saudi government has played in communicating health and substance abuse since the 1980s, when officials realised the need to modernise the means of communicating health and drug issues from mosque-based only to include modern methods such as televised campaigns, school-based programmes and hospital-based health education. Since then, government-led health communication initiatives have been well established in the kingdom. The dissertation is able to demonstrate a critical understanding of the reality of health communication against substance abuse in Saudi Arabia and make a range of recommendations to improve the efficacy of current policies and suggest new avenues for future research